Research on the Intrinsic Sensing Performance of an Optical Fiber Dosimeter Based on Radiation-Induced Attenuation - Junyu Hou; Zhanzu Feng; Ge Ma; Weiwei Zhang; Zong Meng; Yuhe Li (Sensors)
Current research on dosimeters based on radiation-induced attenuation (RIA) primarily focused on enhancing radiation sensitivity or reducing dependencies from interference factors. However, their intrinsic sensing performance has received limited attention. This work proposed application and analysis methods for RIA-based dosimeters, validated by a low-cost apparatus using commercial fibers. Initially, a generic protocol of high-dose detection after low-dose calibration was suggested to overcome the various dependencies of RIA, enabling repetitive monitoring of near-stable radiation by simple replacement of commercial fibers. Experiments comparing three dose-loss models demonstrated that the saturation-exponential model exhibited superior accuracy, achieving absolute errors below 4 Gy within a measurable range of up to ~300 Gy. Subsequently, the system’s RIA-based sensitivity was ~125.6 dB·Gy−1·km−1. The resolution and sensitivity expressed by optical power were newly defined, effectively quantifying the decline in precision and response ratio during detection. Moreover, an additional structure was introduced to extend the measurable range. Simulations and experiments under 1-MeV electron irradiation verified that adjustable ranges could be achieved through configuration of attenuation layers. In summary, these advancements provided critical guidance for component selection and operational evaluation, facilitating the commercialization and practical deployment of RIA-based dosimeters.